2022
DOI: 10.1515/reveh-2022-0085
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide; a neurotoxin in popcorns: a systematic review and meta-analysis

Abstract: Acrylamide is a known neurotoxic compound for humans. Foods that have high concentrations of acrylamide need to be identified. One of the food products containing acrylamide is popcorn. Popcorn is an important source of snacks for children, especially students. The presented study is a systematic review and meta-analysis of the level of acrylamide in popcorn. The search was done in different databases with the keywords; acrylamide, popcorn, popped corn. 27 articles were found by searching various databases. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Also, reliable sources of novel data streams, which are a subset of machine learning, are effective in increasing the efficiency of these methods, which include text data, transactional data, and trade data. These sources can be used in the evaluation of foodborne illnesses, microbial contamination, and chemical, physical, and microbiological hazards in food products ( Wang et al, 2022 , Abedini et al, 2022 ).…”
Section: Methods Of Detecting Fraud In Cheesementioning
confidence: 99%
“…Also, reliable sources of novel data streams, which are a subset of machine learning, are effective in increasing the efficiency of these methods, which include text data, transactional data, and trade data. These sources can be used in the evaluation of foodborne illnesses, microbial contamination, and chemical, physical, and microbiological hazards in food products ( Wang et al, 2022 , Abedini et al, 2022 ).…”
Section: Methods Of Detecting Fraud In Cheesementioning
confidence: 99%
“…A systematic review and meta-analysis showed that AA content in popcorn varied between 1,017.7–106 μg/kg ( 30 ). Also, microwaved popcorn had the lowest levels of AA compared to other preparation methods.…”
Section: Human Exposure To Acrylamidementioning
confidence: 99%
“…Based on the meta-regression, the type of popcorn was an adequate criterion for the AA concentration, and sweet popcorn had higher AA values. The total AA concentration within popcorn has been evaluated as 459.6 ± 220.3 μg/kg ( 30 ). Žilić et al ( 31 ) reported a value of AA in thermally processed corn-based food highly consumed within the market globally that AA concentration in corn flakes, corn/tortilla chips, and popcorn was in the range of 5–6,360 μg/kg < limit of quantification (LOQ) to 2,220 μg/kg, and < LOQ to 1,186 μg/kg, respectively.…”
Section: Human Exposure To Acrylamidementioning
confidence: 99%